Three new records of angiosperms for Bangladesh (Bangladesh Journal of Plant Taxonomy, 2025)
A few of the plant specimens of the family Lauraceae Juss., previously collected from Bandarban and Habiganj districts and stored in DACB, were identified as Lindera assamica (Meisn.) Kurz and Litsea sericea (Wall. ex Nees) Hook.f. Another few specimens of the family Rubiaceae Juss., recently collected from the Lathitila forest of Moulvibazar during the floristic explorations conducted in the northeast region of Bangladesh, were determined to be Acraranthera tomentosa R.Br. ex Hook.f. These species are new to the flora of Bangladesh. Taxonomic descriptions of these species have been provided, together with information on their ecology, distribution, representative specimens examined, and illustrations or photographs.Bangladesh J. Plant Taxon. 32(1): 115-122, 2025 (June)